Pengaruh Penggunaan Selimut Inisiasi Menyusu Dini (SIMDi) terhadap Suhu Tubuh Bayi Saat Inisiasi Menyusu Dini (IMD) - Sudarmi Sudarmi; Supriatiningsih Supriatiningsih; Nora Isa Tri Novadela (Politeknik Kesehatan Tanjung Karang, 2019)
Efforts to launch breast milk (ASI) products by doing Early Breastfeeding Initiation (IMD). Results of Nutrition Status Monitoring (PSG) in 2016, in Lampung province the IMD figure was 48.5 below the national average. The quality of the implementation of IMD in Indonesia was lacking, the achievement of IMD was 51.9% consisting of 42.7% getting IMD in <1 hour after birth, and 9.2% in one hour or more after birth. The aim of the study was to determine the effect of using turtle blanket on infant body temperature during IMD. Research experiment with, type of true experiment, design of pre-post test group design. The population of all babies was born normal, a sample of 60 infants. Data analysis using a two-way Anova test. Results There was a significant difference between the body temperature of the infant group before and after 60 minutes of IMD implementation. With the value of Fcount=44.52 (Ftable=3.92). There was a significant difference between the body temperature of the group of babies given the Turtle Blanket blanket and the group of babies given a contemporary blanket. With the value of Fcount=11.83 (Ftable=3.92) and There is no interaction factor between the treatment of infants and types of blankets. With the value of Fcount=0.83 (Ftable value=3.92).